A Monte Carlo-based radiation safety assessment for astronauts in an environment with confined magnetic field shielding. (20th October 2015) - Geng, Changran; Tang, Xiaobin; Gong, Chunhui; Guan, Fada; Johns, Jesse; Shu, Diyun; Chen, Da
Abstract: The active shielding technique has great potential for radiation protection in space exploration because it has the advantage of a significant mass saving compared with the passive shielding technique. This paper demonstrates a Monte Carlo-based approach to evaluating the shielding effectiveness of the active shielding technique using confined magnetic fields (CMFs). The International Commission on Radiological Protection reference anthropomorphic phantom, as well as the toroidal CMF, was modeled using the Monte Carlo toolkit Geant4. The penetrating primary particle fluence, organ-specific dose equivalent, and male effective dose were calculated for particles in galactic cosmic radiation (GCR) and solar particle events (SPEs). Results show that the SPE protons can be easily shielded against, even almost completely deflected, by the toroidal magnetic field. GCR particles can also be more effectively shielded against by increasing the magnetic field strength. Our results also show that the introduction of a structural Al wall in the CMF did not provide additional shielding for GCR; in fact it can weaken the total shielding effect of the CMF. This study demonstrated the feasibility of accurately determining the radiation field inside the environment and evaluating the organ dose equivalents for astronauts under active shielding using the CMF.